Installation and testing the LOFAR software on ACC Cyfronet cluster Prometheus - Kuligowska, Elzbieta Marzena; Czuchry, Maciej; Chyzy, Krzysztof; Kundera, Tomasz Norbert; Roskowinski, Carole; Dzielak, Marta (Computer Science, 2019)
We present the actual status and the most important issues related to the installation of the data reduction LOFAR software on high power computer Prometheus located in ACC Cyfronet. We refer to the software itself as well its practical use cases in the context of the scientific tool and the detailed installation/testing methodology. We address most typical challenges and problems that occured during our attempts to set up the complete and ready-to-use LOFAR environment (including not only programs, but also libraries, scripts and other additional tools) on non-standard (cluster-type) computing system. The result of these works is then briefly summarized. We also discuss the issues related to LOFAR documentation, maintenance, distribution and further development. Finally, we propose some future improvements.